MARKAZIY OSIYO DAVLATCHILIGIDA QADIMGI BAQTRIYANING TUTGAN O‘RNI - Erkinova Sumayya (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article mainly tells about the foundation, borders and socio-economic life of the ancient Bactrian state. It also provides information about the Bactrian state that existed since time immemorial, given in ancient Greek and Avestan sources, military campaigns conducted by this state, as well as the controversy that took place during the Achaemenid dynasty, and complete information about the cultural life of the Bactrian state mode.